2010
DOI: 10.1111/j.1752-1688.2009.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urban Spatial Structure, Sociodemographics, and Climate on Residential Water Consumption in Hillsboro, Oregon1

Abstract: House‐Peters, Lily, Bethany Pratt, and Heejun Chang, 2010. Effects of Urban Spatial Structure, Sociodemographics, and Climate on Residential Water Consumption in Hillsboro, Oregon. Journal of the American Water Resources Association (JAWRA) 46(3):461‐472. DOI: 10.1111/j.1752‐1688.2009.00415.x Abstract:  In the Portland metropolitan area, suburban growth in cities such as Hillsboro is projected to increase as people seek affordable housing near a burgeoning metropolis. The most significant determinants for incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 33 publications
6
96
0
2
Order By: Relevance
“…For a given place, the determinants reported in past research may not all have significant effects on residential water consumption. For instance, year built, building size, property value, income, and age were not significant determinants for Hillsboro, Oregon [17]. Among 14 independent variables derived from a small data (N = 264) in Melbourne, Australia, only household size, property value, and the number of washing machine loads per week were significant, explaining 60% of the variation in the water consumption [35].…”
Section: Residential Water Consumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…For a given place, the determinants reported in past research may not all have significant effects on residential water consumption. For instance, year built, building size, property value, income, and age were not significant determinants for Hillsboro, Oregon [17]. Among 14 independent variables derived from a small data (N = 264) in Melbourne, Australia, only household size, property value, and the number of washing machine loads per week were significant, explaining 60% of the variation in the water consumption [35].…”
Section: Residential Water Consumptionmentioning
confidence: 99%
“…The study also suggested that water-saving innovations would result in spillover effects across the study region. At the census tract level, House-Peters et al [17] reported that spatial autocorrelation of water consumption existed among neighboring census tracts in Hillsboro, Oregon. In the case of water scarcity, planners and policy makers can use these neighborhood effects as a lever to change people's water-use behavior, and help create a water-saving culture in communities [26].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Agthe and Billings (1987), Arbués and Villanua (2006), Arbués et al (2003), Baumann et al (1998), Gaudin et al (2001), and Hoffmann et al (2006) emphasized the influence of income on domestic water consumption. In reality, domestic water consumption is not only influenced by economic factors but also by socio-demographic factors such as population growth (Morehouse et al 2002), age (Kenney et al, 2008), education (House-Peters et al, 2010), age of building , and number of bed rooms (Fox et al, 2009).…”
Section: Introductionmentioning
confidence: 99%